Analysis of influencing factors and paths of synergistic development of water resources-economic society-ecological environment based on DIM modeling - Suming Ren; Fuqiang Wang; Peiheng Liu; Heng Zhao; Honglu Zhang; Lanbo Cui (Scientific Reports)
Abstract The intersection of climate change and human activities exacerbates the prominent contradiction between environmental resources and economic development. The synergistic development of water resources, economy and society, and ecological environment is particularly urgent. Therefore, accurately identifying its influencing factors and related pathways holds significant practical importance in resolving the contradiction between resources and economic development. This study constructs a system of influencing factors for the synergistic development of “water resources, economic society and ecological environment” from three dimensions, reveals the influencing relationship between indicators through the Decision Making Trial and Evaluation Laboratory (DEMATEL), determines the hierarchical structure of the influencing factors and the related paths through the Interpretive Structural Model (ISM), and classifies the influencing factors through the Matrix Multiplication Method of Cross Influence Matrix Multiplication (MICMAC). The results show that water resource factors are important cause factors and economic, social and ecological factors are essential effect factors. The factors influencing the synergistic development of “water resources, economic society and ecological environment” can be divided into four levels, of which the total water resources, precipitation and NDVI are at the bottom and are the most fundamental factors. The percentage of groundwater supply, total water supply, water resource utilization rate and energy consumption of 10,000 yuan of GDP are the deep core elements. Total grain output, water resources per capita, and water use per capita are the direct influencing factors. Finally, taking the Central Plains Urban Agglomeration as an example, selecting the identified important influencing factors and analyzing the level of synergistic development of its coupled system found that the degree of coupling coordination increased from 0.324 in 2011 to 0.978 in 2020. The water resources system showed a fluctuating change, and it is still the key to synergistic development. Analyzing the relationship between subsystems and clarifying the key factors for synergistic development of coupled systems are important for policy formulation, improving environmental governance and promoting high-quality economic development.